Conceito "retrô" na moda contemporânea: uma análise a partir da sociedade de consumo - Ferreira, Luana dos Santos (2013)
Retro is the term used to refer to past times and, lifestyle, fashion and attitudes portrayed in this. In contemporary society there is a great need for consumption of fashion products with retro concept. In this project, we intend to leave the past in evidence in apparel, including how to use the proceeds of this style in contemporary society, and how this relationship is given by the consumer society. Among the specific objectives, one can present the style of retro fashion on new market trends, understand the frequent use of readings, present a historical overview of fashion and how to apply this style in the development of fashion products for female-century XXI. The methodology to be applied shall be qualitative, exploratory and literature.